PENGARUH PENERAPAN STRATEGI PEMBELAJARAN KOOPERATIF TIPE PAIR CHECKS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI IPA SMAN 1 2x11 ENAM LINGKUNG - Silvia, Berly; Rismen, Sefna; Aima, Zulfitri (STKIP PGRI Sumbar, 2013)
TheÂ backgroundsÂ ofÂ thisÂ researchÂ areÂ theÂ studentsâÂ unwillingnessÂ toÂ shareÂ the informationÂ andÂ theÂ styudentsâÂ lowÂ conceptÂ understandingÂ onÂ theÂ mathematical learning of the grade-XI natural-science class of SMAN 1 2x11 Enam Lingkung inÂ theÂ yearsÂ 2012/2013. TheÂ typeÂ ofÂ researchÂ isÂ experimentalÂ byÂ using Randomized Control Group Only Design. The data analysis technique used is TTest . Techniques of data analysis were performed using one-way t test. Based on the analysis of data obtained t of 4.95 is greater than the amount specified t table 1.64.Â Then theÂ hypothesisÂ inÂ thisÂ researchÂ received.Â InÂ conclusion,Â studentsâ comprehension of math concept that apply cooperative learning Pair Checks than studentsâ comprehension of math concept that apply conventional learning.